2014
DOI: 10.1093/glycob/cwu057
|View full text |Cite
|
Sign up to set email alerts
|

Glycoxidation of biological macromolecules: A critical approach to halt the menace of glycation

Abstract: Glycation is the result of covalent bonding of a free amino group of biological macromolecules with a reducing sugar, which results in the formation of a Schiff base that undergoes rearrangement, dehydration and cyclization to form a more stable Amadori product. The final products of nonenzymatic glycation of biomacromolecules like DNA, proteins and lipids are known as advanced glycation end products (AGEs). AGEs may be generated rapidly or over long times stimulated by distinct triggering mechanisms, thereby … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
57
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 116 publications
(60 citation statements)
references
References 83 publications
3
57
0
Order By: Relevance
“…There are also couple of recent reports for the presence of the auto-antibodies in the sera of the cancer patients which needs to be validated further [37]. Therefore the need of the hour is to stop this dreaded reaction using novel approach like nanoconjugation [38], [39]. Our research group has recently shown some medicinal plants that have potent antioxidant property like Phyllanthus virgatus , Ficus virens and Boerhaavia diffusa [40]–[42].…”
Section: Discussionmentioning
confidence: 99%
“…There are also couple of recent reports for the presence of the auto-antibodies in the sera of the cancer patients which needs to be validated further [37]. Therefore the need of the hour is to stop this dreaded reaction using novel approach like nanoconjugation [38], [39]. Our research group has recently shown some medicinal plants that have potent antioxidant property like Phyllanthus virgatus , Ficus virens and Boerhaavia diffusa [40]–[42].…”
Section: Discussionmentioning
confidence: 99%
“…It is also unknown if the presence of glucose may increase hydrolytic damage. Certainly proteins in general can be harmed by nonenzymatic glycosylation [16]. In the glucose-free gel, glycosylation would not occur but also the interactive subunits are sterically protected by the insertion of the dextran.…”
Section: Resultsmentioning
confidence: 99%
“…Baynes's group proposed that oxidative stress and damage to proteins in diabetes are due to free radicals from the autoxidation of sugars and sugar adducts to protein and as well as of unsaturated lipids in plasma and membrane proteins [48]. This glycation reaction has been highly implicated in redox balance and therefore this type of reaction is designated as a Bglycoxidation reaction^ [48,49]. Our group previously reported that glycation induces apoptosis by provoking oxidative stress in pancreatic beta cells [50,51], therefore, a similar oxidative stress would be expected in other pathological situations such as neurodegenerative diseases.…”
Section: Protein Glycation and Oxidative Stress In Neurodegenerative mentioning
confidence: 99%